Antibiofilm Potential of Medicinal Plants against Candida spp. Oral Biofilms: A Review - Rafaela Guimarães; Catarina Milho; Ângela Liberal; Jani Silva; Carmélia Fonseca; Ana Barbosa; Isabel C. F. R. Ferreira; Maria José Alves; Lillian Barros (MDPI AG, 2021)
The use of natural products to promote health is as old as human civilization. In recent years, the perception of natural products derived from plants as abundant sources of biologically active compounds has driven their exploitation towards the search for new chemical products that can lead to further pharmaceutical formulations. Candida fungi, being opportunistic pathogens, increase their virulence by acquiring resistance to conventional antimicrobials, triggering diseases, especially in immunosuppressed hosts. They are also pointed to as the main pathogens responsible for most fungal infections of the oral cavity. This increased resistance to conventional synthetic antimicrobials has driven the search for new molecules present in plant extracts, which have been widely explored as alternative agents in the prevention and treatment of infections. This review aims to provide a critical view and scope of the in vitro antimicrobial and antibiofilm activity of several medicinal plants, revealing species with inhibition/reduction effects on the biofilm formed by Candida spp. in the oral cavity. The most promising plant extracts in fighting oral biofilm, given their high capacity to reduce it to low concentrations were the essential oils extracted from Allium sativum L., Cinnamomum zeylanicum Blume. and Cymbopogon citratus (DC) Stapf.